Model untuk Menentukan Faktor Utama yang Digunakan untuk Mengukur Biaya Audit - Sarlina Sari (Faculty of Economics, Universitas Internasional Batam, 2020)
This study aims to examine the factors that influence audit fees in manufacturing companies listed on the Indonesia Stock Exchange (BEI). Apart from that, it also aims to build a model for determining and measuring audit fees. In this study, a multiple regression model was developed to test the factors that are expected to affect audit fees (such as: client size, profitability, client risk, client complexity, type of client industry, audit office status, audit report lag, audit rotation and audit committee independence). Data is collected from financial reports and annual reports available on the IDX website for the period 2014 to 2018. The results of this study indicate that the main factors that have a significant effect on audit fees are: audit report lag, risk, client size, audit office status, and company complexity. Audit fees are negatively and significantly related to industry type and profitability. In addition, no relationship was detected between audit committee independence and audit rotation and audit fees.